2006
DOI: 10.1111/j.1365-2222.2006.02451.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucin genes have different expression patterns in healthy and diseased upper airway mucosa

Abstract: These results suggest that NP have a different pattern of mucin expression than healthy NM and that CF polyps (increased MUC5B) and AC polyps (decreased MUC2) have a different mucin expression pattern than bilateral NP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 44 publications
6
79
0
1
Order By: Relevance
“…In our previous study, we found that MUC8 mRNA levels were up-regulated in human nasal polyps epithelium whereas MUC5AC gene was not Yoon et al, 2002]. This is coincident with recently reported studies in which MUC8 expression was highly increased in all studied epithelia and glands of nasal polyp samples compared with the expression of the other major mucin genes, MUC5AC and MUC5B, which are moderately expressed in nasal polyps [Martinez-Anton et al, 2006. These studies raised the possibility that MUC8 plays a major role in the airway mucosa and its over-expression is related to mucus hypersecretion.…”
supporting
confidence: 82%
“…In our previous study, we found that MUC8 mRNA levels were up-regulated in human nasal polyps epithelium whereas MUC5AC gene was not Yoon et al, 2002]. This is coincident with recently reported studies in which MUC8 expression was highly increased in all studied epithelia and glands of nasal polyp samples compared with the expression of the other major mucin genes, MUC5AC and MUC5B, which are moderately expressed in nasal polyps [Martinez-Anton et al, 2006. These studies raised the possibility that MUC8 plays a major role in the airway mucosa and its over-expression is related to mucus hypersecretion.…”
supporting
confidence: 82%
“…The role of MUC8 in the airways is also poorly understood, and, to date, there are no data suggesting that it is altered in lung disease. Expression of MUC8 glycoprotein in upper airways (nasal mucosa and nasal polyps) has been shown to be quite variable and not altered in CF, asthma, or allergic rhinitis (44). The cell surface mucins MUC1, MUC4, and MUC16 are present in both the periciliary and mucus layers of the ASL and are detected in human sputum, accounting for 10% of its mucin content, with the remaining consisting of the gel-forming mucins MUC5AC and MUC5B (56).…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC together with MUC5B are the major contributors to the rheological properties and the structure of the mucus. [46][47][48] MUC2, however, is found concurrent irritation of the nasal mucosa. 2,49) The composition of normal mucus is altered depending on the relative contribution to the secretions of these different cellular sources and the disease stage of the subject.…”
Section: Mucinmentioning
confidence: 99%